Rewiring Photosynthesis by Water‐Soluble Fullerene Derivatives for Solar‐Powered Electricity Generation - Zhu, Huawei (2024)
Natural photosynthesis holds great potential to generate clean electricity fromsolar energy. In order to utilize this process for power generation, it isnecessary to rewire photosynthetic electron transport chains (PETCs) of livingphotosynthetic organisms to redirect more electron flux toward anextracellular electrode. In this study, a semi-artificial rewiring strategy, whichuse a water-soluble fullerene derivative to capture electrons from PETCs anddonate them for electrical current generation, is proposed. A positivelycharged fullerene derivative, functionalized with N,N-dimethyl pyrrolidiniumiodide, is found to be efficiently taken up by the cyanobacterium Synechocystissp. PCC 6803. The distribution of this fullerene derivative near the thylakoidmembrane, as well as site-specific inhibitor assays and transient absorptionspectroscopy, suggest that it can directly interact with the redox centers in thePETCs, particularly the acceptor side of photosystem I (PSI). The internalizedfullerene derivatives facilitate the extraction of photosynthetic electrons andsignificantly enhance the photocurrent density of Synechocystis byapproximately tenfold. This work opens up new possibility for the applicationof fullerenes as an excellent 3D electron carrier in living biophotovoltaics.